2013
DOI: 10.17265/2162-5263/2013.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Quality Assessment of Drinking Water in Tanta City, Egypt

Abstract: Abstract:The physico-chemical and biological (algal and bacterial) quality of tap water in Tanta City were elucidated. Samples were collected during December 2011, covering all the water plants and the areal extension of the pipe line network in Tanta. Total dissolved solids content classifies water origin into surface water, shallow and deep groundwater. Fe, Mn and hardness in some samples of groundwater origin are obviously exceeding the WHO (World Health Organization) limit. Mostly, green algae are found (3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…All the tested water samples showed the chloride value within the given range ascompared to NDWQS. Khalil et al (2013); Shittu et al ( 2008); Ullah et al (2014); Maharjan et al (2020); Ghartimagar et al (2020); Pradhananga et al (1993) and Thapa (1997) also found chloride content for all water samples within guideline value. Chloride can be a marker of pollution and is crucial in identifying sewage contamination of ground water (Purandara2003).Natural sources ,sewage ,industrial effluents ,urban run off including deionizing salts, and saline intrusion are the main sources of chloride in drinking water.…”
Section: Discussionmentioning
confidence: 85%
“…All the tested water samples showed the chloride value within the given range ascompared to NDWQS. Khalil et al (2013); Shittu et al ( 2008); Ullah et al (2014); Maharjan et al (2020); Ghartimagar et al (2020); Pradhananga et al (1993) and Thapa (1997) also found chloride content for all water samples within guideline value. Chloride can be a marker of pollution and is crucial in identifying sewage contamination of ground water (Purandara2003).Natural sources ,sewage ,industrial effluents ,urban run off including deionizing salts, and saline intrusion are the main sources of chloride in drinking water.…”
Section: Discussionmentioning
confidence: 85%
“…The total algae count and algae distribution in water samples were also determined, as previously described by Khalil et al (16) and Rashad et al (2). In brief, samples for algal count were preserved with iodine in potassium iodide (Lugol's Solution), then algae identification was made according to Prescott, Whitford and Schumacher.…”
Section: Water Analysismentioning
confidence: 99%